Complete mitochondrial genome and the phylogenetic position of the Burmese narrow-headed softshell turtle Chitra vandijki (Testudines: Trionychidae) - Chen Chen; Hong Xiaoyou; Li Wei; Yu Lingyun; Chen Haigang; Zhu Xinping (Mitochondrial DNA. Part B. Resources, 2021)
Narrow-headed softshell turtles constitute a group of critically endangered freshwater turtles that belong to the family Trionychidae. Here, we determine the complete mitogenome of the Burmese narrow-headed softshell turtle Chitra vandijki. The length of the mitochondrial genome was 16,614 bp, composed of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and twelve noncoding regions. The phylogenetic analysis strongly indicated that C. vandijki is closely related to C. indica. The mitochondrial genome will contribute to the genetic research and conservation of C. vandijki in the future.